Convenient Michael addition/beta-elimination approach to the synthesis of 4-benzyl- and 4-aryl-selenyl coumarins using diselenides as selenium sources - Padilha, Gustavo (2017)
A concise and efficient, two-step approach toward 4-organoselenyl coumarin derivatives from the easily available 4-hydroxycoumarins, is reported. The synthesis was based on conventional tosylation followed by a tandem selena-Michael addition/β-elimination reaction of an aryl-/benzyl-selenolate anion on the corresponding 4-tosyloxycoumarins. The selenolate anions were conveniently generated in situ by exposure of the corresponding diselenides to NaBH4. Selected compounds demonstrated to exhibit antioxidant properties in mice cortex and hippocampus.